Entrepreneurship : choice or compulsion? - Kee, Shu Jun. (2008)
Our research paper seeks to establish a causality relationship between the poor economy and growing entrepreneurship. It also aims to post some recommendations on measures the Singapore government can take to further promote the spirit of entrepreneurship in Singaporeans and to inculcate in the younger generation a sense of adventure and the courage to pursue their own dreams.